Complexation behavior of Auricularia auricula polysaccharide and whey protein isolate: Characterization and potential beverage application. Issue 3 (18th January 2022) - Zhao, Yunsong; Shui, Dongning; Li, Shengjie; Lin, Xinping; Liang, Huipeng; Zhang, Sufang; Ji, Chaofan
Abstract: The formation of soluble complexes between whey proteins and polysaccharides has potentially useful applications in the beverage industry. In this study, Auricularia auricula polysaccharides (AP) and A. auricula extract (EAA) were prepared and their complexation behavior with whey protein isolate (WPI) was studied at pH 4.7 in order to ensure protein dispersal and avoid precipitation to achieve enhanced WPI stability. Both AP and EAA enhanced stability of 2%–4% WPI via the formation of complexes. WPI‐AP and WPI‐EAA solutions exhibited characteristics resembling steady pseudoplastic fluid. Heat treatment further resulted in altered structures of formed complexes which improved stability. Sensory evaluation by electronic tongue indicated that AP and EAA could relieve astringency of the WPI solution induced in acidic pH. This study provided the theoretical basis and demonstrated the potential application of a novel WPI‐enriched beverage. Practical applications: Functional Auricularia auricula polysaccharides and an A. auricula extract were shown to enhance stability of high concentrated whey protein isolate solutions. In this study, a potential commercially exploitable healthy beverage was developed. Furthermore, the foundation for its production is provided, which does not involve polysaccharide extraction steps thereby preserving the nutritional value of polysaccharide‐rich ingredients.